Impact of Nutritional Patterns on Metabolic Health and Chronic Disease Risk: A Systematic Review - Handayani, Annisa Awalia (Yayasan Sinergi Kawula Muda, 2023)
Non-communicable diseases (NCDs) are a major global health burden, with dietary factors playing a significant role in their prevention and management. This study examines the impact of dietary interventions, particularly the Mediterranean diet, DASH diet, and plant-based diets, on reducing NCD risk. A systematic literature review was conducted using databases such as PubMed, Scopus, and Web of Science to identify relevant studies on the relationship between dietary patterns and NCDs. The findings reveal that adherence to nutrient-rich diets improves metabolic health, reduces inflammation, and lowers the prevalence of cardiovascular diseases, diabetes, and obesity. However, challenges such as limited access to healthy foods, socioeconomic barriers, and gaps in healthcare provider knowledge persist. Policy recommendations include increasing subsidies for nutritious foods, regulating unhealthy food advertising, and integrating dietary education into healthcare systems. Multidisciplinary approaches, including digital health interventions and community-based programs, are necessary to enhance adherence to dietary modifications. Future research should explore the long-term effects of dietary interventions, the role of nutrigenomics, and microbiome-diet interactions in disease prevention. Strengthening dietary strategies in public health and clinical practice is crucial to reducing NCD prevalence and improving global health outcomes.